The efficacy of telephone follow-up frequencies on clinical parameters post non-surgical periodontal therapy: a randomized controlled trial - He, Yinghui; Tang, Feng; Liao, Ruoyi; Hu, Chun; Liu, Hongyu (Frontiers in Oral Health, 2025)
ObjectivesThis randomized controlled trial aimed to investigate the impact of different telephone follow-up frequencies on periodontal clinical parameters after non-surgical periodontal therapy.Materials and methodsPatients with Stage II–IV periodontitis were enrolled and randomly assigned to high-frequency (once every 2 weeks), medium-frequency (once a month), and low-frequency (once in 3 months) follow-up groups. All patients received standard non-surgical periodontal treatment. The full mouth probing depth (PD), clinical attachment loss (CAL), gingival index (GI), and plaque index (PI) were evaluated at baseline, after treatment (T1) and post treatment 3 months (T2).ResultsFrom T1 to T2, the high-frequency follow-up group had significant reduced in PD (p = 0.03), improved in GI (p = 0.04) and PI (p = 0.03) compared with the medium and low-frequency groups. There was no significant difference in PD, GI, and PI between the medium-frequency group and the low-frequency group. No statistical difference was found in CAL among the three groups.ConclusionMore frequent telephone follow-up helps maintain and enhance non-surgical periodontal therapy effects.